1981
DOI: 10.1103/physrevlett.46.539
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Propagation of a Proton Ring

Abstract: A magnetically self-confined ring of 430-keV protons with a field reversal on axis of 3% is formed in an 8-kG solenoid, as evidenced by propagation more than 1 m in 15-400 mTorr air or hydrogen without dispersion. Up to 83% of the proton kinetic energy is in rotation and inductive coupling of axial ring energy to azimuthal plasma current induced in air (but not hydrogen) gives reflection of >50% of the ring from a 23% mirror.PACS numbers: 52.55.Ke Magnetic field configurations in which an externally applied ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

1981
1981
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…A schematic of the system which approximates closely the experimental arrangement of Dreike et al [22][23][24] is shown in Fig. 2.2.…”
Section: Numerical Simulations Of Injection and Trapping Of Ion Ringsmentioning
confidence: 83%
See 1 more Smart Citation
“…A schematic of the system which approximates closely the experimental arrangement of Dreike et al [22][23][24] is shown in Fig. 2.2.…”
Section: Numerical Simulations Of Injection and Trapping Of Ion Ringsmentioning
confidence: 83%
“…For reasons explained in Section 2.9, this was not an ion ring in equilibrium but nevertheless it demonstrated that ion sources of the requisite power and charge are available. A more modest programme at Cornell is directed to the creation of partially field-reversed equilibrium ion rings (f <0.1), Dreike et al [22][23][24].…”
Section: Introduction 1historical Introductionmentioning
confidence: 99%
“…For instance, a commonly used injection scheme for ion ring configurations is cusp injection, 13 where ions injected axially into the device from a ring diode are accelerated azimuthally by the radial component of the magnetic field near the diode. For instance, a commonly used injection scheme for ion ring configurations is cusp injection, 13 where ions injected axially into the device from a ring diode are accelerated azimuthally by the radial component of the magnetic field near the diode.…”
Section: Discussionmentioning
confidence: 99%
“…Образование ионных колец по схеме, представленной на рис. 1, доказано в опытах с протонами [3,4]. Возможность сжатия магнитного потока проверена, например, в эксперименте [5].…”
Section: постановка задачиunclassified
“…По этой причине при вводе пучка нарушается аксиальная симметрия, что является необходимым условием для образования конфигурации с обращенным полем [13,14]. И, действительно, такие кольца образовывались в опытах [3,4]. В более поздних исследованиях, представленных в обзорах [15,16], этот процесс был изучен более детально.…”
Section: вывод дисперсионного уравнения для бесконечно длинного в напunclassified